2020
DOI: 10.2174/0929866527666200127115059
|View full text |Cite
|
Sign up to set email alerts
|

The Renin Angiotensin System and Bipolar Disorder: A Systematic Review

Abstract: Bipolar Disorder (BD) is a chronic a multifactorial psychiatric illness that affects mood, cognition, and functioning. BD is associated with several psychiatric conditions as well clinical comorbidities, particularly cardiovascular diseases. The neurobiology of BD is complex and multifactorial and several systems have been implicated. Considering that the Renin Angiotensin System (RAS) plays an important role in cardiovascular diseases and that recently evidence has suggested its role in psychiatric disorders,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…Finally, we found that genes that are candidates for both domestication and BD are significantly associated to human pathological phenotypes impacting the renin‐angiotensin system (HP:0003351, HP:0000847, HP:0000841, HP:0000848), which is mostly involved in the regulation of blood pressure and electrolyte balance, as well as vascular resistance, but which has been also linked to mood disorders (Mohite et al, 2019). Patients with BD show higher plasma renin activity compared with controls (Barbosa et al, 2020). In animals, the inhibition of selected components of the renin‐angiotensin system reverses the hypertension and cognitive deficits associated with mood disorders (Mohite et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, we found that genes that are candidates for both domestication and BD are significantly associated to human pathological phenotypes impacting the renin‐angiotensin system (HP:0003351, HP:0000847, HP:0000841, HP:0000848), which is mostly involved in the regulation of blood pressure and electrolyte balance, as well as vascular resistance, but which has been also linked to mood disorders (Mohite et al, 2019). Patients with BD show higher plasma renin activity compared with controls (Barbosa et al, 2020). In animals, the inhibition of selected components of the renin‐angiotensin system reverses the hypertension and cognitive deficits associated with mood disorders (Mohite et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…The findings are consistent with those of previous studies [ 7 , 8 , 9 ], illustrating the development of cardiac fibrogenesis and ventricular dysfunction in rats deprived of REM sleep. This study suggests that lithium treatment may rescue cardiac remodeling in patients with bipolar disorder because the profibrotic signaling regulated by lithium in REM sleep-deprived hearts is also involved in the pathophysiology of bipolar disorder [ 18 , 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, genes that are candidates for both domestication and BD are significantly associated to human pathological phenotypes impacting the renin-angiotensin system (HP:0003351, HP:0000847, HP:0000841, HP:0000848), which is mostly involved in the regulation of blood pressure and electrolyte balance, as well as vascular resistance, but which has been also linked to mood disorders (Mohite et al, 2019). Patients with BD show higher plasma renin activity compared to controls (Barbosa et al, 2020). In animals, the inhibition of selected components of the renin-angiotensin system reverses the hypertension and cognitive deficits associated with mood disorders (Mohite et al 2019).…”
Section: Genetic Signatures Of Domestication and The Genetics Of Bdmentioning
confidence: 99%